ANALISIS SENGKETA KOREKSI FISKAL PADA BIAYARESEARCH AND DEVELOPMENT (STUDI KASUSPEMERIKSAAN PAJAK PT.X TAHUN 2014) - Kusumastuti, Hadining; Ruchiyat, Ari Warli (UI Scholars Hub, 2020)
This paper discusses the Fiscal Correction Dispute Analysis on Research & Development Costs at the 2014 Tax Audit Year PT. X. In this case study discusses the different interpretations between taxpayers and Fiscus on the provisions governing the costs that can be charged to companies, causing tax disputes. The purpose of writing is to determine the background of the recognition of research and development costs at PT X. and its compliance with the provisions of tax regulations. The research method used is descriptive qualitative. The result of this case study is the assumption from the Fiscus regarding the recognition of irrelevant research and development costs, while for taxpayers the cost is relevant because it is a cost in the framework of product feasibility testing.